Aligning Islamic Law and Customary Law: Legal Dialectics in the Tradition of Forced Marriage in Jambi - Dinda Difia Madina; Zezen Zainul Ali; Mega Puspita (Justicia Islamica, 2023)
This research will discuss the practice of forced marriage tradition by customary sanctions for returning home late at night in the Lekuk 50 Tumpi Lempur Jambi community. This research will also examine the interaction between Islamic law and customary law on the sanctions of the tradition. The research method used is field research. Data is collected by interviewing 16 informants, 7 couples, and two traditional leaders in Lekuk Lima Puluh Tumbi Lempur Jambi. Furthermore, the data that has been obtained is analyzed. So that the research results found that the interaction of Islamic law and customary law in the tradition of forced marriage in the Lekuk 50 Tumbi Lempur community, First, pre-marriage or imposition of sanctions, the nuances of Islamic law and custom go hand in hand. Second, the marriage contract procession is carried out with the Islamic religion, such as pillars and conditions. Third, post-contract, although the nuances of custom can be said to be more, it does not leave the nuances of religion. Theoretically, this research offers insight into the harmonious and complementary relationship between Islamic law and customary law, which is different because the two laws generally intersect. In addition, practically, this research reveals the practice of forced marriage carried out by custom, not from the family, which generally occurs